Peningkatan Daya Saing Apotek melalui Transformasi Digital Berbasis Sistem Informasi Manajemen - Anton Anton; Cristeddy Asa Bakti; Verdi Eno Ade Irawan; Stefan Daniel Anugrah; Rahadian Ilyasa (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2026)
This community service program aims to improve the competitiveness of Apotek Keluarga, Ungaran, through digital transformation based on a Management Information System. The partner’s main problems are related to pharmacy operational management that has not been fully digitalized, particularly in recording medicine inventory, purchase transactions, sales transactions, stock monitoring, expired medicine control, and operational report preparation. These conditions may lead to recording errors, delays in data retrieval, inaccurate inventory information, and less optimal business decision-making. The implementation method consisted of preliminary observation, partner needs identification, socialization, training, system usage practice, mentoring, monitoring, and evaluation. The results show that the implementation of a Management Information System can assist Apotek Keluarga, Ungaran, in improving the orderliness of records, accelerating data retrieval, strengthening inventory control, monitoring medicines approaching expiration dates, and providing more accurate reports for pharmacy managers. In addition, this activity also improves the partner’s understanding and skills in utilizing digital technology to support pharmacy operations. Therefore, digital transformation based on a Management Information System is an important strategy to enhance efficiency, service quality, and the sustainable competitiveness of Apotek Keluarga, Ungaran.